VD_FINDINFO Jug / 2012 / 298 vom 26. November 2012 - VD Tribunal cantonal (2012)
ADMINISTRATION DES PREUVES, DROIT D'OBTENIR UNE DÉCISION, DROIT D'ÊTRE ENTENDU, INTERDICTION DE L'ARBITRAIRE | 29 Cst., 139 CPP (CH), 147 CPP (CH), 393 al. 1 let. a CPP (CH), 393 al. 2 let. a CPP (CH), 394 let. b CPP (CH)